Coronary angiogenic effect of long-term administration of Nigella sativa - Lubna I. Al Asoom (BMC, 2017)
Abstract Background Coronary angiogenesis is one of the preferable adaptive responses of aerobic training. Previous studies found inotropic and hypertrophic cardiac effects for long-term administration of Nigella sativa (NS), but no studies have explored its coronary angiogenic effect. The present study compared the effect of long-term NS- administration and exercise training on the induction of coronary angiogenesis. Method Fifteen adult male Wistar rats were divided into three groups: control, NS-fed, and exercise-trained (Ex). The NS-fed rats were administered 800 mg/Kg NS orally for eight weeks. The (Ex) rats were trained on a five-lane treadmill at a speed of 18 m/min and a grade of 32° for two hour/day for eight weeks. After the experiment, the hearts were extracted and immunohistological slides were prepared using rat vascular endothelial growth factor (VEGF), platelet endothelial cell adhesion molecule-1 (PECAM-1), Von Willebrand factor (VWF) and nitric oxide synthase-2 (NOS-2) antibodies (Ab). Photomicrographs were analysed using ImageJ software, and the % of the immunostained-area of 10 fields per specimen was recorded. Result VEGF was significantly higher in the NS- (2.59±1.37%) and Ex rats (2.51±1.86%) compared to the control group (1.58±0.78%) with P<0.01. The VWF was significantly lower in the two experimental groups (1.57±0.83%, 1.07±0.72%) for NS and Ex groups respectively, compared to the controls (2.38±1.72) with p<0.01. Only Ex group had a higher PECAM-1 (1.79±0.78%) and lower NOS-2 (0.83±0.57%) than the control group (1.19±1.17%, 1.25±1.19%) for PECAM-1 and NOS-2 with P<0.01 and P<0.05 respectively. Conclusions The present study demonstrated an increase in VEGF and a decrease of the VWF in the hearts of Nigella-fed and exercise-trained rats. This might indicate the potentiality for induction of coronary angiogenesis via long-term administration of NS and exercise training. NS effect on coronary angiogenesis needs to be explored further as it might lead to a new promising preventive and therapeutic agent of the ischemic heart disease.